Search for methodological approaches of organotypic cultivation for following cryopreservation - Kaverinska, Аnna; Tkachenko, Anton; Prokopiuk, Volodymyr (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):307